Analisis Bentuk-Bentuk Bahasa Tulis pada Anak dengan Gangguan Disleksia - Apri Winda Hafifah; Fiamanillah Fiamanillah; M. Rizky Abdullah; Fatmawati Fatmawati; Rhani Febria (UIR Press, 2023)
Psycholinguistics is a branch of linguistics that studies the processes of language formation in humans. Dyslexia is a language disorder that can hinder children's language development. This research was conducted using descriptive method. Interviews, recordings and observations were used as data collection techniques. Based on the explanation above, we can conclude that every child with dyslexia is a unique individual because they have different abilities in recognizing and remembering letters. Dyslexic children are not the same as other dyslexic children.